Using Genetic Algorithm For Eye Location Detection - Ramadan M. Ramo (College of Education for Pure Sciences, 2012)
Abstract In this research a hybrid system has been made to locate the position of eyes in the human face depending on the circular form of the eye. The primary process of image has been done using Gaussian Smoothing Operator to soften the image as well as to decrease the noise in it, then Sobel Operator has also been used to show the ridges. The suggested method is to hybridize the genetic algorithm (GA) together with Hough method to show the circle (CHT) which is recalled as (GCHT). This method has been applied on some models and the result shows that it has high accuracy and high performance in determining the eye position. The research is regarded as a primary level of recognition the for security purposes.